1996
DOI: 10.1002/ana.410390408
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic metabolism and corticospinal tract integrity determine motor recovery in stroke

Abstract: We studied the role of remote metabolic depressions and pyramidal tract involvement regarding motor recovery following a first hemiparetic ischemic stroke. In 23 patients the regional cerebral glucose metabolism (rCMRGlu) was measured with positron emission tomography and the location and spatial extent of the stroke lesions were assessed by magnetic resonance imaging. Motor impairment during the acute and chronic stages (4 weeks after stroke) was determined by a motor score and recordings of magnetic evoked m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
142
2
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(155 citation statements)
references
References 63 publications
(41 reference statements)
8
142
2
3
Order By: Relevance
“…In a number of Most TMS studies have shown that presence of contralaclinical trials, there have been behavioral improvement teral MEPs early after the stroke is a marker for good even in patients with chronic and apparently stable stroke. recovery [2,8,9,20,31,46,53,55,62]. Preservation of corLiepert and co-workers [38,39] have shown that TMS ticospinal tract with MRI imaging was also found to maps increase in size in this circumstance showing that the correlate with good recovery confirming the TMS studies expected cortical changes appear to be occurring.…”
Section: Mechanisms Of Plasticitymentioning
confidence: 82%
See 1 more Smart Citation
“…In a number of Most TMS studies have shown that presence of contralaclinical trials, there have been behavioral improvement teral MEPs early after the stroke is a marker for good even in patients with chronic and apparently stable stroke. recovery [2,8,9,20,31,46,53,55,62]. Preservation of corLiepert and co-workers [38,39] have shown that TMS ticospinal tract with MRI imaging was also found to maps increase in size in this circumstance showing that the correlate with good recovery confirming the TMS studies expected cortical changes appear to be occurring.…”
Section: Mechanisms Of Plasticitymentioning
confidence: 82%
“…Preservation of corLiepert and co-workers [38,39] have shown that TMS ticospinal tract with MRI imaging was also found to maps increase in size in this circumstance showing that the correlate with good recovery confirming the TMS studies expected cortical changes appear to be occurring. [2]. Clearly, contralateral control, even if reorganized, Another method for improving rehabilitation is the seems superior to ipsilateral control in recovery.…”
Section: Mechanisms Of Plasticitymentioning
confidence: 99%
“…23 There is a consensus that mechanisms of remote degeneration are critical for the overall clinical profile in many acute CNS pathologies. 24 In this study, we examined the function of autophagy and its kinetics during apoptosis in an in vivo model of acute focal CNS lesion, focusing on remote changes that are induced by hemicerebellectomy (HCb). 22 HCb is a unique experimental paradigm in which axonal damage-induced neuronal death mechanisms can be studied.…”
Section: Do Not Distributementioning
confidence: 99%
“…Also, remote metabolic depression could be responsible for hypoperfusion and this has been shown within 1 week after focal ischemia (Watanabe et al, 1998;Barbelivien et al, 2002). In stroke patients, thalamic hypometabolism is thought to result from depressed synaptic activity (diaschisis) due to acute structural damage in the infarcted cortex (Binkofski et al, 1996).…”
Section: Hypoperfusion At the Acute Phase In The Cortex And Thalamus mentioning
confidence: 99%